Morphogenetic peculiarities of reproductive biology in sugar beet (Beta vulgaris L.) breeding - T. P. Zhuzhzhalova; A. A. Nalbandyan; E. N. Vasilchenko; N. N. Cherkasova (Вавиловский журнал генетики и селекции)
This review considers the processes of morphogenesis used in the development of propagation methods and the creation of a new starting material for sugar beet. It has been demonstrated that methods of particulation, in vitro microcloning and cell breeding that reflect non-sexual forms of plant reproduction increase the effectiveness of breeding experiments. The review describes the in vitro culture methods maintaing a tendency in plants for vegetative propagation and stimulating increase in genetic variability of properties when mutagens such as ethyl methanesulfonate, alien genetic structures with mf2 and mf3 bacterial genes in Agrobacterium tumefaciens strains, and selective agents (Сd++ ions and abscisic acid) are incorporated into plant cells. It presents the results of using fluorescent microscopy, cytophotometry, biochemical analysis and determining the level of phytohormones and content of nucleic acids in nuclei for forecasting the seed setting ability. It has demonstrated that long self-pollination of plants causes decrease in fertility of pollen grains, resulting in the sterilization of male gametes and the appearance of pistillody flowers. Self-fertile plants isolated from these lines serve as sterility fixers, while the apomixis elements increased the ovule number, additional embryo sacs and embryos. A role of apomixis in contributing to variability in the ontoand phylogenetic development of plants have been substantiated. The review reflects the morphological features of the in vitro development of sexual and somatic cells in embryos during the formation of seedlings based on floral and vegetative embryoidogeny. Use of the SNP and SSR (Unigenes) molecular-genetic markers having a high polymorphism level has appeared effective to characterize the developed breeding material and hybrid components when carrying out crossings. The study of sugar beet starting materials for the presence of TRs mini-satellite loci making it possible to reveal O-type plants-pollinators (sterility fixing agent) and MS-form plants are of interest for breeding as well. The selected material can be widely used in breeding to produce hybrids, allowing for a 2–3-fold reduction of the development period. The review also discusses the prospects for the development and implementation of new methods and original schemes in sugar beet genetics, biotechnology and breeding.